Ant Communities along a Gradient of Plant Succession in Mexican Tropical Coastal Dunes - Patricia Rojas; Carlos Fragoso; William P Mackay (Sociobiology)
Most of Mexican coastal dunes from the Gulf of Mexico have been severely disturbed by human activities. In the state of Veracruz, the La Mancha Reserve is a very well preserved coastal community of sand dunes, where plant successional gradients are determined by topography. In this study we assessed species richness, diversity and faunal composition of ant assemblages in four plant physiognomies along a gradient of plant succession: grassland, shrub, deciduous forest and subdeciduous forest. Using standardized and non-standardized sampling methods we found a total of 121 ant species distributed in 41 genera and seven subfamilies. Grassland was the poorest site (21 species) and subdeciduous forest the richest (102 species). Seven species, with records in ≥10% of samples, accounted 40.8% of total species occurrences: Solenopsis molesta (21.6%), S. geminata (19.5%), Azteca velox (14%), Brachymyrmex sp. 1LM (11.7%), Dorymyrmex bicolor (11.2%), Camponotus planatus (11%) and Pheidole susannae (10.7%). Faunal composition between sites was highly different. Nearly 40% of all species were found in a single site. In all sites but grassland we found high abundances of several species typical of disturbed ecosystems, indicating high levels of disturbance. A species similarity analysis clustered forests in one group and grassland and shrub in another, both groups separated by more than 60% of dissimilarity. Similarity of ant assemblages suggests that deciduous and subdeciduous forests represent advanced stages of two different and independent successional paths.